Towards lean product and process development - Khan, Muhammad Sharjeel; Al-Ashaab, Ahmed; Shehab, Essam; Haque, Badr; Ewers, Paul; Sorli, Mikel; Sopelanad, Amaia (Taylor & Francis, 2013)
Successes in lean manufacture have led researchers and practitioners to consider extending ‘lean' to different parts of the engineering enterprise, including product and process development (PPD). Lean product development (PD) has been understood to mean lean manufacture applied to PD, while the roots of lean PD - just like lean manufacture - go back to Toyota. This article presents the methodology adopted in order to pave the way towards a coherent lean PD model that combines lessons from the Toyota product development system (TPDS) with other best practises. The article provides a unique review of the lean PD research area, and a reference framework for the enablers that Toyota has employed for lean PD. An investigation of five engineering enterprises undertaken to search for evidence of the implementation of lean PD enablers through observation, document analysis and interviews is also presented. Some enablers have been informally applied, while few have been formally implemented, and no model was found to formally combine lean PD enablers into a coherent whole. This is the first article to critique attempts to describe lean PD and provide a definition for Lean PD.
Keywords: lean product development, Toyota development, product development, product design, set based concurrent engineering, continuous improvement, process modelling, design for manufacture, process innovation, knowledge based engineering